2020
DOI: 10.1007/s11120-019-00706-w
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic characterization and expression profiles of sugarcane infected by Sugarcane mosaic virus (SCMV)

Abstract: Sugarcane mosaic virus (SCMV), belonging to genus Potyvirus, family Potyviridae, is a severe pathogen of several agricultural important crops, mainly sugarcane. Due to complex nature of sugarcane, the effect of SCMV pathogenicity on sugarcane photosynthetic systems remains to be explored. In this study, we investigated the alterations occurring in the photosynthetic system in the sugarcane genotypes at the cytopathological, physiological and biological, transcriptome and proteome level. We generated the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
0
16
1
Order By: Relevance
“…Sugarcane yellow leaf disease (SYLD) and sugarcane mosaic disease (SMD) are the most reported viral diseases, so far. Sugarcane streak mosaic virus (SCSMV, unassigned genus, family Potyviridae ), Sorghum mosaic virus (SrMV, genus Potyvirus , family Potyviridae ) and Sugarcane mosaic virus (SCMV, genus Potyvirus , family Potyviridae ) have been reported to cause SMD (Akbar et al, 2021). SCMV has been reported to be distributed, worldwide (Gemechu et al, 2006), whereas SrMV is mainly found in China, United States and Vietnam (Ha et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugarcane yellow leaf disease (SYLD) and sugarcane mosaic disease (SMD) are the most reported viral diseases, so far. Sugarcane streak mosaic virus (SCSMV, unassigned genus, family Potyviridae ), Sorghum mosaic virus (SrMV, genus Potyvirus , family Potyviridae ) and Sugarcane mosaic virus (SCMV, genus Potyvirus , family Potyviridae ) have been reported to cause SMD (Akbar et al, 2021). SCMV has been reported to be distributed, worldwide (Gemechu et al, 2006), whereas SrMV is mainly found in China, United States and Vietnam (Ha et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Typical symptoms of wilt disease include leaf wilting, yellowing, restricted growth, red discoloration of the xylem vessels to stem or root decay (Okungbowa & Shittu, 2012). to cause SMD (Akbar et al, 2021). SCMV has been reported to be distributed, worldwide (Gemechu et al, 2006), whereas SrMV is mainly found in China, United States and Vietnam (Ha et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…is the most important sugar and energy crop worldwide [ 1 , 2 , 3 ]. Sugarcane mosaic disease is widespread in sugarcane-growing countries [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and causes heavy yield losses [ 16 , 17 ]. In the 1920s, sugarcane mosaic disease almost collapsed the sugar industry in Argentina, Brazil, and Louisiana [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 1920s, sugarcane mosaic disease almost collapsed the sugar industry in Argentina, Brazil, and Louisiana [ 18 ]. Although sugarcane mosaic disease is controlled by planting resistant sugarcane cultivars, it continues to be a threat to the sugarcane industry [ 4 , 15 , 17 , 19 ]. The main causal agents for the sugarcane mosaic disease are Sugarcane mosaic virus (SCMV), Sorghum mosaic virus (SrMV), and Sugarcane streak mosaic virus (SCSMV), which belong to the Potyviridae family, with SCMV and SrMV being members of the Potyvirus genus [ 20 ], whereas SCSMV is a member of Poacevirus genus [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation